Ordinance No. 5, § 1, Kahlotus Town Council (1907) (Kahlotus, Washington). - (:unkn) unknown (My University, 1907)
All persons (except Police Officers and other persons whose duty it is to execute or process warrants or make arrests) who shall carry upon their persons any concealed weapon, consisting of revolver, pistol or other fire-arm (except by a written permit from the Town Marshall) or any knife (other than an ordinary pocket knife), metal knuckles or any dirk or dagger or sling shot or any instrument by the use of which injury can be afflicted upon any person or property of any other person.All persons (except Peace Officers as aforesaid) who shall draw, exhibit or attempt to use any deadly weapon upon, to or against another person in said town with intent to do bodily injury to any such person. All persons (except Peace Officers as aforesaid and persons practicing at target shooting in shooting gallery duly licensed) who shall within the town limits fire off and discharge any gun, pistol or firearm of any kind, or bomb."
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE